PROSPEK PENGEMBANGAN KOMODITAS PERKEBUNAN DI WILAYAH BOLIYOHUTO KABUPATEN GORONTALO - Rival Rahman; Dwi Putro Tedjo Baskoro; Boedi Tjahjono (TATALOKA, 2015)
Agricultural land use planning is essential for a region in developing their agricultural commodities. Boliyohuto region is a region which has the potential for very large land resources, especially for the development of agricultural commodities.The purpose of this study was to see how the development prospects of plantation commodities in the commodity Boliyohuto based economic development as well as physical resources of land. Data analysis method used is the image interpretation, Location Quotient (LQ) and Shift Share Analysis (SSA) to determine the main commodity and Land Suitability Analysis.The analysis showed the extent of the potential for development of superior commodities is an area of 24.655 ha. Then seeded commodities in this region are coconut, coffee, cocoa and cotton. Based on the results analsisi land suitability, land suitability classes for each commodity is moderately suitable (S2), marginally suitable (S3), and is not suitable (N). From these results, the prospects for the development of plantation commodities in the region Boliyohuto covers, palm development potential area of 16133.44 hectares, an area of 13159.41 ha of coffee, and cocoa area of 13543.94 ha.